2014
DOI: 10.3390/polym6030755
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of Antiproliferative Agents via Stents

Abstract: Abstract:A stent is a medical device for serving as an internal scaffold to maintain or increase the lumen of a body conduit. Stent placement has become a primary treatment option in coronary artery disease for more than the last two decades. The stenting is also currently used for relieving the symptoms of narrowed lumen of nonvascular organs, such as esophagus, trachea and bronchi, small and large intestines, biliary, and urinary tract. Local delivery of active pharmaceutical agents via the stents can not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 75 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…Stent insertion can be a lifesaving procedure affording dramatic, emergent relief of acute respiratory distress from airway obstruction resulting extended survival (Hohenforst-Schmidt et al, 2016;Shaffer and Allen, 1998). PU membrane generally has a high tensile strength allowing them as a covering material for bronchotracheal stents that are compressed inside an introducer tube with a minimum volume during the delivery to the obstructed lumen (Kwon and Park, 2014;Lamba et al, 1997;Seo and Na, 2014). Anti-cancer drugs loaded in PU polymeric coating of stents are locally released to inhibit the growth of the tumor while simultaneously minimizing systemic drug exposure (Puranik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stent insertion can be a lifesaving procedure affording dramatic, emergent relief of acute respiratory distress from airway obstruction resulting extended survival (Hohenforst-Schmidt et al, 2016;Shaffer and Allen, 1998). PU membrane generally has a high tensile strength allowing them as a covering material for bronchotracheal stents that are compressed inside an introducer tube with a minimum volume during the delivery to the obstructed lumen (Kwon and Park, 2014;Lamba et al, 1997;Seo and Na, 2014). Anti-cancer drugs loaded in PU polymeric coating of stents are locally released to inhibit the growth of the tumor while simultaneously minimizing systemic drug exposure (Puranik et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent excessive tissue hyperplasia and the resulting reobstruction of the stented lumen, localized drug delivery via the stent has been attempted, and many antiproliferative drugs, including sirolimus and paclitaxel, are proven effective for lowering the restenosis rate of the procedure. In addition to antiproliferative drugs, some small interfering RNAs (siR-NAs) have been effectively employed to suppress tissue hyperplasia after stenting [12][13][14][15]. siRNAs can be incorporated into a stent-covering for localized siRNA delivery to the tissue around the stent.…”
Section: Introductionmentioning
confidence: 99%
“…Published data from meta-analyses and clinical trials comparing DES to BMS suggested higher rates of late clinical events in patients receiving DES [ 14 17 ]. The antiproliferative drugs released by DES interfere with the natural vascular healing process by arresting the endothelial cell proliferation and growth on the stent surface [ 18 ]. Late (30 days – 1 year) and very late (>1 year) stent thrombosis are the major clinical consequences of impeded endothelial healing in patients receiving DES [ 19 ].…”
Section: Introductionmentioning
confidence: 99%